Remmittances, Banking Sector Development and Economic Growth in Fiji - Sami, Janesh (International Journal of Economics and Financial Issues, 2013)
This study examines the role of remittances and economic growth in banking sector development in Fiji using annual data from 1980-2010. This study finds evidence of long run relationship between banking sector development, remittances and economic growth using bounds testing procedure developed by Pesaran et al. (2001). In addition, our causality analysis based on vector error correction model (VECM) and Toda Yamamoto Granger Non Causality test (1995) suggest that there is causality from economic growth and remittances to banking sector development. The study indicates that remittances inflows may not be only important for economic growth but also for development of banking sector. It is thus, important for policymakers to ensure that remittances flow through formal channels. Keywords: Remittances; Economic growth; Banking sector development; Bounds testing procedure JEL Classifications: C32; F24; O16